Electric Word Of Mouth (Ewom) Effect On Brand Equity - غدير باسم; صالح كنان (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aimed to study the effect of the electric word of mouth (eWOM) on brand equity and brand attitude. A questionnaire was designed and conducted on a convenient sample of restaurant customers in Lattakia Governorate, where 240 questionnaires were distributed and 229 questionnaires were retrieved, of which 224 valid for the study. The research concluded that there is a positive effect of electric word of mouth on brand equity and brand attitude, in addition; there is a positive effect of brand attitude on brand equity. The research also concluded that the brand attitude mediates the effect of the electric word of mouth on the brand equity, as the electric word of mouth affects brand equity through its effect on brand attitude.